The Effect of Target Variation Training on Service Skills in the Volleyball Game of Students in Dukuh Menanggal, Surabaya - Reinaldus Juliano Cadul; Luqmanul Hakim (Green Publisher Indonesia, 2026)
The low accuracy of overhead service skills in volleyball among students is often caused by monotonous and less varied training methods, which reduce motivation and limit skill development. This research aims to examine the effect of target variation training on overhand service skills in volleyball among 30 fifth-grade students at SD Negeri Dukuh Menanggal 1/424 Surabaya. The primary research problem is the low accuracy of students' services caused by monotonous training methods. This research utilizes a quantitative experimental method with a one-group pretest-posttest design. Data were collected through overhand service skill tests and analyzed using a paired t-test via the SPSS 23 program. The results showed an increase in the mean score from 10.43 (pretest) to 12.27 (posttest). Based on the hypothesis test, a significance value of 0.000 < 0.05 was obtained, leading to the acceptance of Ha. It can be concluded that target variation training significantly influences the improvement of students' accuracy, consistency, and service control. Teachers are encouraged to apply this method as an innovative and effective learning alternative